STATISTICAL TENDENCIES OF WOMEN’S AND MEN’S SCIENTIFIC CAREERS IN LITHUANIA AND FINLAND: COMPARATIVE ANALYSIS - Novelskaitė, Aurelija; Purvaneckienė, Giedrė (Acta Paedagogica Vilnensia, 2009)
The paper is devoted for comparative analysis of women’s and men’s participation in two rather different scientific communities such as Lithuania and Finland. The aim of the paper is two-fold. First, to evaluate Lithuanian situation in the context of other country. Comparison of Lithuanian and Finland is meaningful here because despite the countries have rather different political and economical achievements, socio-cultural traditions, and socio-historical heritage, they both are members of European Union; also both countries belong to the one geographical region. Secondly, to compare Lithuanian and Finnish situation in the context of gender equality achievements in the country. The comparison is trying to answer a question about effect of focused gender equality policy onto women’s involvement into scientific community in general and, more specifically, about women-scientists’ possibilities to achieve the highest levels of academic hierarchies.Three main sources of statistical data were used: on the national level – information from statistical data base on Lithuanian scientists as well as statistical information published by national dept. of statistics, and (b) KOTA – statistical data base on Universities in Finland; on international level, – statistical information which was published by European Commission in 2003 and 2006.Analysis of the materials demonstrates, in general, both Lithuanian and Finnish scientific communities experienced rapid feminization around 2000. However, despite the feminization was faster in Lithuania and women composed slightly larger portion among scientists in all fields of science in the country, Finland was doing better in terms of women-scientists’ achievements reaching the highest levels of national academic hierarchy. Credible explanations of the similar tendencies of feminization and different achievements of women scientists in two countries are different. That is, the main reason behind feminization in Lithuanian (as well as in other post-soviet countries) scientific community is diminished status of science in the society (unattractiveness of scientific careers, men’s retreat from the field). Supposedly, feminization of Finnish scientific community was a direct outcome of active gender equality focused policy in the field and in the country in general.
Keywords: gender; scientific career; women’s scientific career; European Union